Application of the Mechanic program in determining the main parameters of the electromechanical drive of the lifting platform - Kopylov A.Z.; Lavrov V.Yu.; Lychagin Yu.V.; Osipov V.I. (Научно-технический вестник Брянского государственного университета)
The article considers the issue of designing at an early stage electromechanical drive of the lifting platform, which is a set of asynchronous frequency-controlled electric motor, two-stage involute bevel gear and lever mechanism scissor type. At the preliminary stage of designing the electromechanical drive of the lifting platform, its structure, types of engines and mechanisms included in it, as well as the main technical characteristics of the drive were determined. In particular, we determined the parameters of the linkage (geometric and mass-inertial characteristics), gear reducer (geometrical parameters, modules, numbers of teeth, gear ratio), carried out the choice of motor, calculation is made of kinematical and power characteristics, as well as dynamic study of the drive. The preliminary design was carried out using the Mechanic program, which does not require significant resources of a personal computer. As a result of the pre-design study, a schematic and structural solution of the lifting platform and electromechanical drive was formed, and their main technical characteristics were determined. As a result, it was proved that the use of the Mechanic program can be effectively applied at the initial stages of the design of the lifting platform, as well as various lifting and transport mechanisms and machines.